2014
DOI: 10.1371/journal.pone.0107424
|View full text |Cite
|
Sign up to set email alerts
|

Thymidylate Synthase Genotype-Directed Chemotherapy for Patients with Gastric and Gastroesophageal Junction Cancers

Abstract: BackgroundRetrospective studies indicate associations between TSER (thymidylate synthase enhancer region) genotypes and clinical outcomes in patients receiving 5-FU based chemotherapy, but well-controlled prospective validation has been lacking.MethodsIn this phase II study (NCT00515216 registered through ClinicalTrials.gov, http://clinicaltrials.gov/show/NCT00515216), patients with “good risk” TSER genotypes (at least one TSER*2 allele) were treated with FOLFOX chemotherapy to determine whether prospective pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…One small genotype directed clinical trial clinical trial evaluated FOLFOX chemotherapy in 25 patients with TS 2R containing genotypes (2R/2R and 2R/3R) and found that radiological response rates did not differ compared to historical control. (33) However, based on our results only the 2R/2R genotype would benefit from this approach; this was also suggested in subgroup analysis of that study. As patients with 3R containing genotypes did not appear to benefit from fluoropyrimidine based chemotherapy in MAGIC, we suggest that alternative treatment options should be evaluated for these patients.…”
Section: Discussionmentioning
confidence: 53%
“…One small genotype directed clinical trial clinical trial evaluated FOLFOX chemotherapy in 25 patients with TS 2R containing genotypes (2R/2R and 2R/3R) and found that radiological response rates did not differ compared to historical control. (33) However, based on our results only the 2R/2R genotype would benefit from this approach; this was also suggested in subgroup analysis of that study. As patients with 3R containing genotypes did not appear to benefit from fluoropyrimidine based chemotherapy in MAGIC, we suggest that alternative treatment options should be evaluated for these patients.…”
Section: Discussionmentioning
confidence: 53%